Genetic Parameters Estimated in the Early Growth of Dimorphandra mollis Benth. Progenies - Porfírio, Kennedy de Paiva; Ribeiro, Andressa; Farias, Séfora Gil Gomes de; Sousa, Thais Santiago de; Ciccheto, Diego Felipe; Barroso, Priscila Alves; Santos, Fabio Sandro dos; Silva, Dandara Yasmim Bonfim de Oliveira [UNESP]; Ferraz Filho, Antonio Carlos (MDPI, 2024)
The extractivism of Dimorphandra mollis Benth., which is a native tree from the Brazilian Cerrado biome, popularly known as fava d’anta, combined with the reduction in native vegetation area in the country over the years may result in a decrease in the specie’s natural populations. The objective of this study was to estimate the quantitative genetic parameters in nursery, hardening, and field phases, based on a progeny test. The experimental design adopted was randomized blocks (six blocks for the nursery and hardening phases, and four blocks for the field phase with 5 plants/plot and 72 mother trees), with evaluations of the collar diameter and seedling height at 30, 90, 150, 480, and 570 days after sowing, between the production and planting phases. Among the coefficients of variance, the phenotypic and additive ones showed the highest values. Heritabilities for height ranged from moderate to high (0.15 to 0.43), indicating good genetic control of the traits, high potential for selection, and possibility of genetic gains. The genetic divergence of the progenies resulted in division into five groups, confirming the existence of genetic variability among the evaluated progenies and the potential for conservation and breeding programs.
Keywords: genetic conservation; mixed linear model; multifunctional forests; native species